Early Fibrinolysis Associated with Hemorrhagic Progression Following Traumatic Brain Injury. Issue 6 (December 2017) - Karri, Jay; Cardenas, Jessica C.; Matijevic, Nena; Wang, Yao-Wei; Choi, Sangbum; Zhu, Liang; Cotton, Bryan A.; Kitagawa, Ryan; Holcomb, John B.; Wade, Charles E.
ABSTRACT: Background: Progressive hemorrhagic injury (PHI) is common in patients with severe traumatic brain injury (TBI) and is associated with worse outcomes. PHI pathophysiology remains poorly understood and difficult to predict. We performed an exploratory analysis aimed at identifying markers in need of further investigation to establish their predictive value in PHI following TBI. Methods: We performed a retrospective chart review of prospectively collected data from 424 highest-level activation trauma patients from January 2012 through December 2013. Patients with severe TBI, defined as head acute injury scale (AIS) score ≥3 and intracranial hemorrhage (ICH) on initial CT, were included. Stable hemorrhage (SH) and PHI was determined by measuring ICH expansion on repeat CT within 6 h. Of 424 patients evaluated, 72 met inclusion criteria. Twenty-five patients had repeated samples available and were dichotomized into SH (n = 6, 24%) and PHI (n = 19, 76%). Levels of plasminogen, urokinase and tissue plasminogen activators (uPA, tPA), plasminogen activator inhibitor-1, α2-antiplasmin (α2AP), and D-Dimers (DD) were measured upon admission and 2, 4, and 6 h later. Results: Longitudinal models identified tPA and DD as positively associated and α2AP inversely associated with PHI. High DD levels are strongly associated with developing PHI over time. Using the full TBI cohort of N = 72, receiver operating curve analysis provided a cutoff of 3.04 μg/mL admission DD to distinguish SH from PHI patients. Conclusion: Our findings support a relationship between markers of fibrinolysis in polytrauma patients with severe TBI and PHI, warranting further investigation into the potential for novel, predictive biomarkers.